2019
DOI: 10.1029/2019gl083195
|View full text |Cite
|
Sign up to set email alerts
|

Topside Ionospheric Disturbances Detected Using Radio Occultation Measurements During the August 2017 Solar Eclipse

Abstract: The CASSIOPE (also known as Swarm‐E) satellite crossed the path of totality of the August 2017 eclipse at ~640‐km altitude ~10 min following the lunar umbra. Observations from CASSIOPE's Global Positioning System radio occultation receiver reveal total electron content variations of 0.2–0.3 total electron content units in the topside ionosphere—a signature of medium‐scale (100‐200 km) plasma disturbances in the lunar penumbra that were induced by the eclipse. The variations were only observed during the eclips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Previous in situ measurements at high altitudes have shown that model electron temperature differ from observations albeit following the height distribution overall shape (Hairston et al, 2018). Moreover, topside eclipse measurements of ion composition, velocity, and temperature (Yau et al, 2018) and TEC using the radio occultation technique (Perry et al, 2019) are also not well reproduced by various ionospheric models. Future work will be required to evaluate the model performance by comparing our results to satellite observations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous in situ measurements at high altitudes have shown that model electron temperature differ from observations albeit following the height distribution overall shape (Hairston et al, 2018). Moreover, topside eclipse measurements of ion composition, velocity, and temperature (Yau et al, 2018) and TEC using the radio occultation technique (Perry et al, 2019) are also not well reproduced by various ionospheric models. Future work will be required to evaluate the model performance by comparing our results to satellite observations.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the Great American Eclipse, which passed through the continental United States from northwest to southeast on 21 August 2017, offered a rare opportunity to study the midlatitude ionosphere and thermosphere response in detail with unprecedented dense observational instruments. Besides the above‐mentioned eclipse effects, a number of interesting findings were reported as well, such as large‐scale TEC and NmF 2 depletion for more than 50% (e.g., Cherniak & Zakharenkova, 2018; Coster et al, 2017; Reinisch et al, 2018), traveling ionospheric disturbances and thermospheric wave (e.g., Eisenbeis et al, 2019; Harding et al, 2018; Mrak et al, 2018; Nayak & Yiǧit, 2018; Pradipta et al, 2018; Zhang et al, 2017), enhanced and long‐lasting posteclipse response (e.g., Lei, Dang, et al, 2018; Wu et al, 2018), and topside ionosphere composition change and interhemispheric ion flows (e.g., Perry et al, 2019; Yau et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Coster et al, 2017;He et al, 2018;Cherniak & Zakharenkova, 2018). Examples of particularly notable regional effects include bow-shaped ionospheric waves (Zhang et al, 2017;Liu et al, 2011) and other atmospheric wave induced fluctuations (Sun et al, 2018;Nayak & Yigit, 2018;Perry et al, 2019;Eisenbeis et al, 2019), ionospheric features arising from radiation inhomogeneity on the solar disk (Mrak et al, 2018), and the polar region impact . Global scale eclipse effects, however, have to date been largely based on theoretical estimates and need to be validated with solid observational evidence.…”
Section: Introductionmentioning
confidence: 99%